BOOSTING STUDENTS’ READING COMPREHENSION THROUGH TEAM PAIR SOLO - Istiadah Istiadah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
This research attempts to enhance the students’ achievement in reading comprehension through Team Pair Solo strategy. By employing classroom action research, this research was conducted in two cycles in which cycle I comprised four meetings and cycle II consisted of two meetings. 28 students of class X3 SMAN I Paciran were purposively selected to be the research subject. Their reading achievement was measured in the form of reading comprehension test (quantitative data). This research also employed diary notes, observation sheet and questionnaire showing that the Team Pair Solo strategy in the classroom was well-implemented. The results of the reading comprehension tests conducted in all cycles obtained better improvements. The students were active, interested and enthusiastic in reading. The research result delineated that Team Pair Solo strategy significantly improved students’ reading comprehension achievements. وتهدف هذه الدراسة إلى تحسين إنجاز الطلاب في فهم المقروء من خلال استراتيجية فريق الزوج منفردا (Team Pair Solo). تستخدم هذه الدراسة تصميم بحث الطبقة الذي يقام في دورتين، تتكون المرحلة الأولى من أربع جلسات وتتكون المرحلة الثانية من جلستين. عينة الدراسة تكونت من 28 طالبا في الفصل X-3 بالمدرسة الثانوية الحكومية باجيران (SMAN Paciran). وتنقسم آلات جميع البيانات إلى اثنتين؛ فالبيانات الكمية باختبار فهم المقروء، والبيانات الكيفية المذكرات اليوميات، وأرواق الملاحظة، والاستبيان. ودل اختبار فهم المقروء على أن نتائج الطلاب تزداد في كل احتبار. بالإضافة إلى ذلك، أظهرت المذكرات، وأوراق الملاحظة، والاستبيان أن عملية التعلم يسير على ما يرام. والطلاب كانوا في النشطة، والاهتمام والحماس عند القراءة. واستخلص هذه الدراسة على أن استراتيجية فريق الزوج منفردا تحسن إلى حد كبير في تحقيق إنجاز القراءة لدى الطلاب.